Three dimensions of musical-biographization: exploring automedial musical practices through reported experiences (Orfeu, 2025)
This study emerged from participants’ accounts of experiences in short-term courses offered during the XVIII Regional Meeting of ABEM Centro-Oeste and within the extension project Musical-Biographization in Music Education. This work establishes a dialoguebetween music education and (auto)biographical research, underpinned by the philosophy of language. Through the reflexivity fostered by automedial musical practices, we seek to understand how such practices contribute to the concept of musical-biographization. To this end, we examined the impact of the reflections articulated in participants’ experience reports following the automedial practices conducted in the formative mini-courses. From this analysis, three dimensions of musical-biographization emerged: the art of listening, the art of encounter, and the art of care. These dimensions became discernible only through experimentation in automedial musical practice. They are consistently supported, as theory informs practice, and practice, in turn, shapes lived experience as expressed through narrative accounts.
Keywords: musical-biographization; automedial musical practices; experience reports; mini-courses